Prehistoric evolution of the dualistic structure mixed rice and millet farming in China. (December 2017) - He, Keyang; Lu, Houyuan; Zhang, Jianping; Wang, Can; Huan, Xiujia
Compared with the monistic structure of crop agriculture in Southwest Asia and Mesoamerica, agriculture in ancient China reflects the characteristics of a dualistic structure with millet in the north and rice in the south. It is argued that the rice and millet farming modes were mutually exchanged during their development and formed a vast region of mixed farming. However, the time and place of its origin, the routes of dissemination, and the development patterns and possible influence factors of mixed farming remain unclear. This study systematically collected information from 804 sites with millet and rice records and detailed floatation results from 78 mixed farming sites in prehistoric China. Three north–south communication corridors are identified between the upper, middle and lower Yellow and Yangtze River Valleys that began around 5500 BP, 8400 BP and 4600 BP, respectively. Cultural communication accompanied by human migration and the unique natural environment of loess and East Asia monsoons facilitated the interaction between millet and rice farming through these corridors. As a comprehensive reflection of the interaction between millet and rice farming, the crop structure of the four core mixed farming regions is in a continual process of adjustment, with the selection of foxtail millet in the southward spread of millet agriculture and temperate Oryza japonica in the northern spread of rice agriculture.